Influencia de los suelos en la dinámica de transferencia de nutrientes en la interfase suelo-agua en un embalse tropical - Arias, Tatiana; Rodriguez Loaiza, Diana Catalina; Peñuela, Gustavo (Ingeniería, 2020)
Context: The construction of a reservoir implies flooding different types of soil, which generates a concentration gradient that favors nutrient transfer from the soil to the water column. Soils provide the reservoir with an important nutrient input, which, along with other sources, contributes to the eutrophication process. Method: This study evaluated, under anoxic conditions, the dynamics of nitrogen and phosphorus transfer at a soil-water interface using three types of soil, which was prior to the flooding process of a tropical reservoir. Batch tests were carried out and monitored for periods of 30 days. Results: The results indicated that the maximum phosphorus concentration in the water-soil interface was reached on day 24, on day 15 for ammoniacal nitrogen, and on day 30 for nitrate, where the soil associated with the high plant cover Rastrojo (Ra) had the highest nutrient intake in all trials. Conclusions: It was found that the transfer of nutrients is associated with the degradation of organic matter present in soils, as well as with the reduction of dissolved oxygen, which favors a greater release of ammonia from the soil to the water. Furthermore, it was found that the transfer gradient was proportional to the type of soil texture. Acknowledgments: The authors gratefully acknowledge the financial support provided by the Colombian Scientific Program, within the framework of the Ecosistema Científico call for proposals (Contract Nr. FP44842-218- 2018). In addition, they thank the company ISAGEN and GDCON group at the University of Antioquia for their funding through agreement 47/26: “Quantifying GHG Emissions for the Sogamoso Hydroelectric Project”.